Pengembangan Sumber Daya Manusia Petani Kopi Melalui Kemitraan dengan Pondok Pesantren Ihya’us Sunnah Al-Hasany, Kab. Jember - Ma'arif, Alia Replica; Soedarto, Teguh; Syah, Mirza Andrian (Universitas Galuh, 2024)
Human resource development (HRD) is very important for coffee farmers because it has a direct impact on increasing coffee productivity and quality. This study aims to identify the partnership pattern between coffee farmers and Pondok Pesanten Ihya'us Sunnah Al-Hasany, factors affecting the performance of coffee farmers, and human resource development strategies for coffee farmers in Tugusari Village. The sampling technique was carried out using purposive sampling method with the criteria that coffee farmers partner with Ihya'us Sunnah Islamic Boarding School. Respondents taken amounted to 34 respondents. The Quantitative approach uses the SEM-PLS Method, while qualitative uses descriptive methods, SWOT analysis and QSPM. The partnership that exists between coffee farmers and the Ihya'us Sunnah Al-Hasany Islamic Boarding School is an agribusiness operational cooperation pattern approach (KOA) and a general trade partnership pattern. The agreement variable (X1), the technical guidance variable (X3), and the product marketing guidance variable (X4) have a positive and significant effect on the partnership (Y1). Meanwhile, the variable of tool assistance (X2) has no positive and insignificant effect on the partnership (Y1). Partnership variable (Y1) has a positive and significant effect on the performance of farmers (Y2) in Tugusari Village. SWOT analysis there are 10 alternative strategies for developing human resources of coffee farmers in partnership patterns with Ihya'us Sunnah Al-Hasany Boarding School, while the results of the QSPM matrix there are 5 strategies generated in developing human resources of coffee farmers in partnership patterns with Ihya'us Sunnah Al-Hasany Boarding School.